Design and implementation of remotely Tigris river water monitoring system in Baghdad - F. Fawzi, Sura; A. Mohammed, Hussein (International Journal of Engineering and Technology, 2018)
Tigris River in Baghdad city that penetrate the rural and urban areas is polluted by many organic substances from different user activities including industrial, agricultural, and domestic purposes. Therefore to monitor and protect the river water from pollution, a remote monitoring system for Tigris river water in Baghdad is suggested. Different water quality parameters; Dissolved oxygen (DO), Electrical conductivity (EC), Total Dissolved Solids (TDS), and PH are measured from two areas near the Tigris River; oil refinery and power station. It show that wastes from these stations are polluted the river with their industrial wastes.Â